2021
DOI: 10.3390/vaccines9070779
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Activity of Sera from Sputnik V-Vaccinated People against Variants of Concern (VOC: B.1.1.7, B.1.351, P.1, B.1.617.2, B.1.617.3) and Moscow Endemic SARS-CoV-2 Variants

Abstract: Since the beginning of the 2021 year, all the main six vaccines against COVID-19 have been used in mass vaccination companies around the world. Virus neutralization and epidemiological efficacy drop obtained for several vaccines against the B.1.1.7, B.1.351 P.1, and B.1.617 genotypes are of concern. There is a growing number of reports on mutations in receptor-binding domain (RBD) increasing the transmissibility of the virus and escaping the neutralizing effect of antibodies. The Sputnik V vaccine is currently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 45 publications
7
69
0
3
Order By: Relevance
“…Also, a Russian study showed that the neutralising activity of sera from persons vaccinated with Sputnik V against the variants of concern was reduced [ 40 ]. For the Beta, Gamma and Delta variants, a statistically significant reduction in neutralising activity of 3.1, -2.8-, and 2.5-fold, respectively, was observed.…”
Section: Consmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, a Russian study showed that the neutralising activity of sera from persons vaccinated with Sputnik V against the variants of concern was reduced [ 40 ]. For the Beta, Gamma and Delta variants, a statistically significant reduction in neutralising activity of 3.1, -2.8-, and 2.5-fold, respectively, was observed.…”
Section: Consmentioning
confidence: 99%
“…However, it should be noted that a study that used data on all symptomatic sequenced cases of COVID-19 in England to estimate the proportion of cases with Delta and Alpha variants according to the patients’ vaccination status, found that Comirnaty was 88.0% effective against symptomatic disease from the Delta variant two weeks after a second dose, compared to 93.7% effective against the Alpha strain, while Vaxzevria was 67.0% effective against the Delta variant, compared to 74.5% effective against the Alpha variant over the same period [ 53 ]. As already mentioned, the virus-neutralizing activity of sera obtained from people vaccinated with Sputnik V showed 2.5-fold reduction for Delta variant [ 40 ]. Although reductions in virus-neutralizing activity are not directly correlated to a vaccine’s overall effectiveness at preventing infection, antibody evasion of Delta variant may contribute to the rapid spread of this variant.…”
Section: Differentiation Between Sputnik V and Some Other Vaccinesmentioning
confidence: 99%
“…J&J observed similar antibody-neutralizing activity upon a single-dose of Ad26.COV2.S against this VOC as compared to the parental USA-WA1/2020 [141]. Similarly, Sputnik V full-vaccination induced equivalent neutralization titers against this variant as the reference strain B.1.1.1, locally endemic to Moscow [142].…”
Section: Effectiveness Of Adenovirus-based Vaccines Against Variantsmentioning
confidence: 73%
“…Real-world data from Canada showed that one dose with AZD1222 has a protective effectiveness of 82% against hospitalization or death from infection with Beta/Gamma [116]. Consistently to AZD1222, one-log reduction in the neutralization activity in sera from J&J vaccinated participants in comparison with the reference isolate and with sera from individuals fully vaccinated with Sputnik V, neutralization titers dropped by 3.1-fold [141,142]. This emphasizes the requirement of more specific vaccines against this variant.…”
Section: Effectiveness Of Adenovirus-based Vaccines Against Variantsmentioning
confidence: 85%
“…However, a report looking at an outbreak of gamma among employees of a goldmine in French Guiana noted a “strikingly high attack rate” among people fully vaccinated with the Pfizer vaccine, as 60% of the fully vaccinated people became infected, compared with 75% of unvaccinated miners without a history of infection 12. The manufacturers of Sputnik V claim that it is “highly effective” against variants including gamma, but a study published in July looking at antibody responses found reduced neutralising activity against gamma and other variants 13…”
Section: Gammamentioning
confidence: 99%